A low-profile dual-polarized UHF antenna based on metasurfaces - Nurul Raihana Abdul Razak (2019)
This project focuses on using two conventional antenna with logarithmic spacing and height– Log-Periodic Dipole Array (LPDA) and Log-Periodic Monopole Array (LPMA) – which are integrated into one single model. The proposed antenna will be dual-polarized, which uses two direction of polarisation which are the vertical and horizontal polarisation. The LPDA acts as the horizontally polarised component while the LPMA acts as the vertically component. A 180 ° phase shifter by using a meandering microstrip feeding line is used for the adjacent monopoles. All the elements of the antenna are parallel to each other in the same plane, displaying a maximum radiation along the axis of the array. This characteristic is known as end-fire antenna. A low-profile characteristic of the antenna is also used in the design. A prototype will be fabricated and tested at the end of the simulation using ANSYS electronics software.